Religious Recognition Arrangements for Penghayat Kepercayaan Sapto Darmo: A Legal Analysis - Iman Pasu Purba; Warsono; Maya Mustika; Agus Satmoko Adi; Rinda Usmi; Imam Wahyudi (Technium Social Sciences Journal, 2023)
Indonesia has a diversity of religions and beliefs that must be maintained. Freedom of religion and belief is a human right whose fulfilment cannot be diminished under any circumstances. The Indonesian Constitution expressly guarantees this right. However, in practice for believers, civil and political rights are often hampered in fulfilment, especially from an administrative aspect. Adherents of the faith often experience obstacles in terms of marriage administration, management of Identity Cards, birth certificates, Family Cards, education rights, and others. this happens because the regulation of religious recognition in Indonesia is still experiencing legal problems. This study was conducted to find out how the legal consequences of regulating religious recognition for penghayat kepercayaan Sapto Darmo. This research uses normative legal research with a descriptive qualitative approach. Primary and secondary legal materials will be analysed to answer the formulation of the study. As a result, religious recognition arrangements in Indonesia still focus on mainstream religious groups only and recognition of believers is still experiencing a legal vacuum (vacuum of norm) in Indonesia.